Indonesia's Defense Diplomacy Towards France in 2019-2023 from Defense Diplomacy Motives Perspective - Jamilah, Kinanti Maryam; Sari, Deasy Silvya (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
The dynamics in the regional and global scope encourage countries to implement defense diplomacy to achieve national defense and security interests. Indonesia is one of the countries that has implemented defense diplomacy and cooperated with many partners spread across various countries. However, from 2019 to 2023, Indonesia's defense diplomacy and cooperation strengthened with one country, France. This research aims to find out the motives of Indonesia's defense diplomacy towards France in the 2019-2023 period. This research uses a qualitative method with the concept of defense diplomacy motives from Frega Wenas Inkiriwang. The research uses data from books, journal articles, news, reports, and documents from official websites. The research data collection technique was conducted through literature studies and interviews. The results show that the motives of Indonesia's defense diplomacy towards France focus on the motives of strategic engagement, confidence-building measures, capacity building, and international reputation to overcome problems, such as inadequate defense equipment, limited defense technology, unfulfilled MEF I and II targets, lack of human resources capable of mastering defense technology, and the interests of maintaining the integration of the Republic of Indonesia. This study found that Indonesia should keep developing diplomatic connections with France to strengthen the defense industry's capabilities and the competency of the Indonesian National Military personnel. Nevertheless, the Indonesian government must establish a monitoring mechanism for cooperation in procuring defense equipment and staff training. This guarantees the continuation of the cooperation agreement, which promotes Indonesia's defense capabilities and independence. Indonesia is not intended to become dependent on France due to the ongoing collaboration; instead, it is designed to assist in developing national defense.